Lakefront : public trust and private rights in Chicago - Kearney, Joseph D.; Merrill, Thomas W. (Ithaca [New York] : Cornell University Press, 2021)
"A history of how Chicago's lakefront, with its parkland and Lake Shore Drive, has come to be. Beginning with the mid-nineteenth century, this book considers both local and broader social, economic, and legal forces, with particular emphasis on the conflict between public and private rights"--
The Lake Front Steal -- The Lake Front Case -- The watchdog of the lakefront -- The struggle for Streeterville -- Reversing the Chicago River -- North Lake Shore Drive -- South Lake Shore Drive and bridging the river -- The transformation of the public trust doctrine -- The lakefront today
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on April 23, 2021).
JSTOR
Keywords: Lakeshore development -- Illinois -- Chicago -- History; Lakeshore development -- Social aspects -- Illinois -- Chicago; Lakeshore development -- Economic aspects -- Illinois -- Chicago; Lakeshore development -- Law and legislation -- Illinois -- Chicago; Rives -- Aménagement -- Illinois -- Chicago -- Histoire; Rives -- Aménagement -- Aspect social -- Illinois -- Chicago; Rives -- Aménagement -- Aspect économique -- Illinois -- Chicago; ARCHITECTURE -- Urban & Land Use Planning; Lakeshore development; Lakeshore development -- Law and legislation; Illinois -- Chicago; Chicago lakefront, History of Lake Shore Drive, Chicago's Lake Michigan shoreline, Montgomery Ward, Streeter/Streeterville, Grant Park; History